Aquatic macrophytes of Itaipu Reservoir, Brazil: Survey of species and ecological considerations - Thomaz, Sidinei Magela (1999)
In a survey of the aquatic macrophytes of the Itaipu Reservoir, we identified 62 taxa in 25 families and 42 genera. The highest number taxa was observed for the emergent macrophytes (40 taxa). Reduced fluctuation in water level, increased light penetration, and sediment enrichment by nutrients and organic matter following the formation of the reservoir favored the appearance of a species-rich community of submerged macrophytes (23% of the taxa identified). The aquatic macrophytes were found mainly near the mouths of the main tributaries of the reservoir, in shallow area of depth less than 2 meters. In addition to the shallow depth, the greater nutrient input from the tributaries and relative protection from wind explained this distribution. Among the species found, Egeria najas merits mention for its occurrence in all localities sampled, with biomass values varying between 98 and 186 gDW/m2. Some potential nuisance species such as Eichhornia crassipes, Salvinia auriculata, and Pistia stratiotes also deserve attention, since they were also observed to be covering large areas of Itaipu Reservoir. © 1999, Paraná Institute of Technology Publication.